Pengaruh Pursed LIP Breathing Dan Sustained Maximal Inspiration Terhadap Peningkatkan Kekuatan Otot Pernapasan Untuk Mengurangi Keluhan Sesak Napas Pada Kasus Kardio Respirasi - Agung Wahyu Permadi; Antonius Tri Wahyudi (Poltekkes Kemenkes Surakarta, 2017)
Abstract : Sustained Maximal Inspiration, Pursed Lip Breathing, Shortness Of Breath. Currently lung disease is a major cause of chronic morbidity and mortality worldwide, many people suffer from this disease for many years and die prematurely due to unhealthy lifestyles such as smoking and work environments that are exposed to much air pollution due to under-employed workers personal protector. One sign of lung disease is airway obstruction in nonreversible or partial reversible airway. One result of lung disease is a lack of respiratory muscle strength resulting in complaints of shortness of breath. Disturbances or complaints of breathlessness can occur towards inspiration or expiration. There is a theory of the effect of breathing exercises on respiratory muscle enhancement in people with shortness of breath. In this study was conducted with the aim to prove the provision of Sustained maximal inspiration (SMI) and pursed lip breathing (PLB) to increase respiratory muscle strength in patients with shortness of breath. This research uses true experimental research with pre-test and post-test design. The study was conducted at the physiotherapy laboratory located in Tabanan, Badung and Denpasar with a sample of 17 patients who experienced complaints of shortness of breath. The number of research subjects was grouped randomly in one group. In this study the group was given treatment as much as 1 time a week and performed for 24 weeks. The expected result of this study was to reduce complaints of shortness of breath without the use of medicines from doctors in cases of cardio respiration